Modeling of Geomechanical Processes from Open Pit to Underground Mining with Complex Morphology - Bekbergenov, Dossanbay; Jangulova, Gulnar; Zeinullin, Abdikarim; Zhanakova, Raissa; Shagirova, Karlygash; Atalykova, Nazym; Kurmanbayev, Olzhas (Civil Engineering Journal, 2025)
The relevance of this study is the need to optimize the transition from open-pit to underground mining in mines with complex deposit morphologies, such as the Akzhal Mine. This is essential to ensure the safety of mining operations and to prevent adverse manifestations of rock pressure and mass cave-ins when changing the type of mining. This study aimed to develop a geomechanical basis for selecting an optimal mining system for the transition from open-pit to underground mining. Particular attention is paid to rock mass stability and its behavior during mining operations, which makes it possible to optimize the parameters of the mining system by considering the characteristics of a mine with a complex deposit morphology. This study used methods to assess the strength of the rock mass, including the concept of the geological structure of the natural environment, the methodology of determining the structural weakening coefficient, and the determination of the rock mass deformation modulus using the fracturing ratio and stability of the rock mass coefficient with an analytical functional relationship of geo-structural factors. The study results made it possible to systematize the rock mass by stability categories and proposed recommendations for the safe operation of deposits during the transition to underground mining, on the choice of mining system, and on the design of its elements. The novelty of this study lies in an integrated approach for predicting the behavior of rock mass and selecting the optimal mining system, which makes it possible to improve the safety and efficiency of production under difficult geological conditions.